The determinant of agriculture development in Indonesia - Aminuddin Anwar (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2022)
Abstract Purpose – This study aims to analyze the determinants of agriculture in Indonesia, represented by the variables of labor, land, fertilizer, and rainfall from 1991 to 2018. Methods – This study uses the time series method by utilizing aggregate data at the national level in Indonesia. The method used in this research is the cointegration and error correction model (ECM). Findings – The results of this study indicate that in the short term, the factors that determine agricultural conditions in Indonesia are the amount of land and the use of fertilizers which show a positive impact. Meanwhile, the long-term results show that all variables, namely labor, land, fertilizer, and rainfall, impact agricultural conditions in Indonesia. The adjustment in the short-term to long-term process is shown that there is an adjustment for agricultural conditions in Indonesia. Implication – This study indicates that the policies carried out by the government in the agricultural sector are important for internal aspects, namely labor, land, and fertilizer, and external effects such as climate change so that appropriate policy interventions can increase agricultural production in Indonesia. Originality – This research contributes to modeling the determinants of the agricultural sector in Indonesia with the error correction model (ECM). Abstrak Tujuan – Penelitian ini bertujuan untuk menganalisis determinan pertanian di Indonesia yang diwakili oleh variabel tenaga kerja, tanah, pupuk, dan curah hujan tahun 1991 sampai dengan tahun 2018. Metode – Penelitian ini menggunakan metode time series dengan memanfaatkan data agregat tingkat nasional di Indonesia. Metode yang digunakan dalam penelitian ini adalah kointegrasi dan error correction model (ECM). Temuan – Hasil penelitian ini menunjukkan bahwa dalam jangka pendek faktor yang menentukan kondisi pertanian di Indonesia adalah jumlah lahan dan penggunaan pupuk yang menunjukkan dampak positif. Sementara itu, hasil jangka panjang menunjukkan bahwa semua variabel yaitu tenaga kerja, tanah, pupuk, dan curah hujan mempengaruhi kondisi pertanian di Indonesia. Penyesuaian dalam proses jangka pendek ke jangka panjang menunjukkan adanya penyesuaian kondisi pertanian di Indonesia. Implikasi – Penelitian ini menunjukkan bahwa kebijakan yang dilakukan pemerintah di bidang pertanian penting untuk aspek internal yaitu tenaga kerja, lahan, dan pupuk, serta terhadap dampak eksternal seperti perubahan iklim sehingga intervensi kebijakan yang tepat dapat meningkatkan produksi pertanian di Indonesia. Orisinalitas – Penelitian ini berkontribusi dalam memodelkan determinan sektor pertanian di Indonesia dengan model error correction model (ECM).